Fast axonally transported proteins in regenerating goldfish optic axons - Perry, GW (J Neurosci, 1987)
Fast axonal transport of protein was examined in regenerating goldfish optic axons after a lesion of either the optic tract or optic nerve, which revealed changes in the original intact optic axon segments or in the newly regenerated axon segments, respectively. In animals killed either 6 or 24 hr after injection of 3H-proline into the eye, labeling of total fast-transported protein in the original axon segments was increased by 2 d after the lesion, reached a peak of nearly 20 X normal at 2 weeks, and then declined to a level somewhat above normal at 12 weeks. When the labeling of individual transported proteins was examined by 2-dimensional gel electrophoresis, it was found that no new labeled proteins appeared during regeneration, but all proteins examined showed an increase in labeling. Among the various proteins, there was great variation in the magnitude and time course of the labeling increase. The largest increase, to nearly 200 X normal with 6 hr labeling, was seen in a protein with a molecular weight of 45 kDa and a pl of about 4.5, resembling a protein that has previously been designated a “growth-associated protein” (GAP-43; Skene and Willard, 1981a). The proteins showing increased labeling included a small fraction of cytoskeletal proteins (alpha-tubulin, beta-tubulin, and actin) that was apparently transported at a much faster rate than is usually expected of these constituents. In the new axon segments, the total protein labeling was increased by 1 week after the lesion, remained elevated at a nearly constant level of about 7 X normal from about 2 to 5 weeks, and then declined to levels somewhat above normal by 12 weeks. The 45 kDa protein again showed the largest increase, and became the single most prominently labeled constituent in the new axons. On the basis of the time course of labeling in both original and new axon segments during regeneration, the fast-transported proteins were tentatively separated into 5 classes that may represent groups of proteins that are coregulated during regeneration. They may conceivably correspond to different functional or structural entities within the neuron.